The poor insane Ophelia: reconsidering Ophelia syndrome - Carlos A. Soto-Rincón; Sergio A. Castillo-Torres; Diego A. Cantú-García; Ingrid Estrada-Bellmann; Beatriz Chávez-Luévanos; Alejandro Marfil (Arquivos de Neuro-Psiquiatria)
ABSTRACT The association between memory loss and Hodgkin's lymphoma has been given the eponym of Ophelia syndrome, in memory of Shakespeare's character in The Tragedy of Hamlet, Prince of Denmark. Nevertheless, there are differences between the disease and the character. Objective: To review the origins and uses of the eponym through an original article by pathologist Ian Carr, its relation to the character Ophelia, and the related autoantibodies. Methods: Historical narrative review. Results: Besides an eloquent description in the original article, Carr presaged the presence of autoantibodies, before they had been thoroughly researched. Since then, five different autoantibodies (mGluR5, Hu, NMDAR, SOX, PCA2) have been associated with Hodgkin's disease. It is interesting to note the divergent outcomes of Shakespeare's character and the patient in the original description by Carr, the latter recovering to lead a normal life, and the former deceased. Conclusions: Although there is little relationship between the fictional character and the syndrome, both imply the unintentional trigger of self-harm (suicide in one case, autoimmunity in the other), thus remaining associated.